E-034 Beyond large vessel occlusion strokes: distal occlusion thrombectomy. (23rd July 2017) - Grossberg, J; Rebello, L; Bouslama, M; Haussen, D; Frankel, M; Nogueira, R
Abstract : Introduction: Endovascular therapy is the standard of care for the treatment of proximal large vessel occlusion strokes (LVOS). Its safety and efficacy in the treatment of distal intracranial occlusions has not been well studied. Methods: We retrospectively reviewed a prospectively collected endovascular database (September 2010-December 2015, n=898) for all patients with distal intracranial occlusions treated with endovascular therapy. Distal occlusions were defined as any occlusion of the anterior cerebral artery (ACA), any occlusion of the posterior cerebral artery (PCA), or any occlusion at or distal to the middle cerebral artery (MCA)-M3 opercular segment. Results: Distal occlusions were treated in 70 patients. The mean age was 66+/-14% and 57% of the patients were male. Thirty-one (44%) of the patients received IV-tPA. The median pre-procedure NIHSS was 19 (IQR, 13–23). The distal occlusion was the primary treatment location in 54 patients and in 16 patients the distal occlusion was treated as a rescue strategy after successful treatment of a proximal LVOS. The locations of the primary cases were MCA-M3 (n=21), ACA with a concomitant MCA-M1 or MCA-M2 (n=16), ACA alone (n=9), PCA (n=6), and ACA with a concomitant MCA-M3 (n=2). The locations of the rescue cases were MCA-M3 (n=8), ACA (n=7), and both MCA-M3 and ACA (n=1). The most common treatment modalities employed were intra-arterial tPA (n=37, 52%), small (3 mm) stent-retrievers (n=24, 33%), and thromboaspiration (n=30, 42%). Near or complete reperfusion (mTICI 2b-3) was achieved in 56 cases (80%). Overall, there were 5 (7%) cases of any parenchymal hematoma (PH). However, two of the PHs were in patients with both a MCA-M1 and an ACA occlusion, and both of these hemorrhages were in the MCA territory. Thus only 3 PHs (4.3%) occurred in the territory of the treated distal occlusion with two of these patients also receiving IV tPA. At 90 days, 24 patients (40%) had a mRS of 0–2 and 13 (21%) had died. Conclusions: Distal intracranial occlusions can be treated safely and successfully with endovascular therapy. Although promising our results need to be corroborated by larger prospective controlled studies. Disclosures: J. Grossberg: None. L. Rebello: None. M. Bouslama: None. D. Haussen: None. M. Frankel: None. R. Nogueira: None.